2007
DOI: 10.1590/s0037-86822007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Características de Vibrio parahaemolyticus isolados de mexilhões (Perna perna) comercializados em Niterói, Rio de Janeiro

Abstract: O ecossistema marinho é o habitat natural de bactérias como Vibrio parahaemolyticus, um importante patógeno causador de gastrenterite humana associada ao consumo de alimentos marinhos. Na presente investigação, foi avaliada a presença de V. parahaemolyticus a partir de 86 amostras de mexilhões in natura e pré-cozidos. Vibrio parahaemolyticus foi isolado a partir de 11,6% dos mexilhões in natura e pré-cozidos avaliados. Todas as cepas avaliadas demonstraram-se urease positivas e 28,5% Kanagawa positivas sugerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…In our work, and that of Chen et al (2005), collections were made during cold months, which might have influenced the number of bacterial isolates obtained. Our results were lower in comparison to the studies of Vieira et al (2004) and Pereira et al (2007), which were conducted in climates with warmer temperatures. V. parahaemolyticus is most frequently found in estuaries, sediments, mollusks, and crustaceans (ICMSF, 1978).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our work, and that of Chen et al (2005), collections were made during cold months, which might have influenced the number of bacterial isolates obtained. Our results were lower in comparison to the studies of Vieira et al (2004) and Pereira et al (2007), which were conducted in climates with warmer temperatures. V. parahaemolyticus is most frequently found in estuaries, sediments, mollusks, and crustaceans (ICMSF, 1978).…”
Section: Discussioncontrasting
confidence: 99%
“…obtained in SP where the climate is considered subtropical, as well as in the region where our work was performed, in which the microorganism was isolated from 4.61% (6 of 130) of the analyzed samples. Pereira et al (2007) isolated V. parahaemolyticus from 11.6% of 86 mussel (Perna perna) samples from the town of Niterói, Rio de Janeiro (RJ), which has a tropical climate. In Fortaleza, Ceará, where the climate is semiarid, Vieira et al (2004)analyzed90 samples of freshwater crabs (Ucides cordatus), of which 8.9% tested positive for V. parahaemolyticus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, V. parahaemolyticus infections have increased globally 28,33 . Studies in Brazil demonstrated the presence of V. parahaemolyticus in environmental samples from a variety of sources as well as in clinical samples 1,25,26,27,31,34,35,38 . In 2002, according to data of the National Health Foundation (FUNASA), in Ceará, Brazil, an outbreak of gastroenteritis occurred, and Kanagawa-positive strains of V. parahaemolyticus serovar O3:K6 were isolated 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Hc030 and Hc3060 protein fractions inhibited the growth of V. parahaemolyticus, an important gram-negative pathogen that causes human gastroenteritis associated with seafood consumption without appropriate cooking (Pereira et al 2007, Su & Liu 2007. So, plant-derived proteins would be a good source of antibacterial compounds.…”
Section: Discussionmentioning
confidence: 99%